2011
DOI: 10.1007/s00404-011-2150-0
|View full text |Cite
|
Sign up to set email alerts
|

Variability of total thiol compounds, oxidative and nitrosative stress in uncomplicated pregnant women and nonpregnant women

Abstract: This study provides information about the changes in plasma levels of many variables having important role in pregnancy complication during all trimesters in uncomplicated pregnancy compared with nonpregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…The rise in serum sFlt-1 levels observed in our study as gestation progresses, is consistent with several studies19,39,41. It is likely that this elevation is due to increasing placental ischemia and oxidative stress occurring during pregnancy, indicative of angiogenic restriction, and controlled vascular permeability42, and is corroborated by others39,43,44.…”
Section: Discussionsupporting
confidence: 92%
“…The rise in serum sFlt-1 levels observed in our study as gestation progresses, is consistent with several studies19,39,41. It is likely that this elevation is due to increasing placental ischemia and oxidative stress occurring during pregnancy, indicative of angiogenic restriction, and controlled vascular permeability42, and is corroborated by others39,43,44.…”
Section: Discussionsupporting
confidence: 92%
“…Further, it has been proposed that oxidative stress provokes the release of sFlt-1 to a similar or greater extent than hypoxia [37]. Various longitudinal studies have shown increasing oxidative stress during pregnancy [38], [39], [40]. We have earlier reported a positive association between oxidative stress and sFlt-1 in preeclampsia [8].…”
Section: Discussionmentioning
confidence: 77%
“…The idea has, nonetheless, been broadly documented by biomedicine. Thus, for instance, it is very well established that pregnant women endure higher serum levels of lipid peroxidation when compared to non-pregnant women (Little et al, 1999;Ozkan et al, 2012), and that this is accompanied by an increase in serum lipids (e.g., Toescu et al, 2002;Sarandöl et al, 2004). We highlighted the importance of assessing the covariance between MDA and triglyceride concentrations to interpret the lipid oxidative damage measurements (Romero-Haro and Alonso-Alvarez, 2014; Pérez-Rodríguez et al, in press).…”
Section: Discussionmentioning
confidence: 94%